Analysis of Tax Morale and Tax Awareness in the Context of Generations Theory - Mustafa Topsakal; Erdal Gümüş (Maliye Çalışmaları Dergisi)
Based on the context of generational theory, this study aimed to determine individual thoughts about factors affecting tax morale and tax awareness. In this context, participants living in Eskisehir and representing the X, Y, and Z generations responded to varied propositions delivered to them using the questionnaire method. The obtained data were analyzed using the Kruskal–Wallis and Mann–Whitney U tests. The findings revealed that the opinions of Generation Z participants differed from the views of Generations X and Y. In particular, Generation Z evinced the lowest scale average in perceiving the payment of taxes as a sacred moral and ethical duty and attaining moral comfort through the payment of taxes. The study further found that faithful adherents to religious beliefs do not perceive themselves as more capable of complying with taxation. Participants also stated that tax evasion may be viewed as a normal behavior when taxation is regarded as unfair or when economic problems intensify. Conversely, 60% of the participants in the 15–24 age range stated that they would consider paying their taxes in full and do not plan to evade taxes in the future. The study’s results are expected to guide the policy-making efforts of the tax administration. In this context, the study will contribute to the enhancement of the tax morality and tax awareness of citizens.